The Chaos of Fragments, the Fragments of Chaos The Last Prosaic Work of M. Yu. Lermontov: Shtoss - Posta, Andrea (Slavica, 2021)
The unfinished short story, Shtoss received little attention from critics, despite of the fact that it is actually the last prosaic text written by M. Yu. Lermontov. It has become somewhat forgotten because it was interpreted as nothing more than a literary joke the young poet played on his friends in St. Petersburg a few months before his tragic death. This article is a narratological analysis of the short story Shtoss based on the terminology used by Gerard Genette and Boris Uspensky. It also aims to interpret the possible function of fragmentation, absence and uncertainty in the short story.